Sea-Ice Thickness North Hemisphere CryoSat-2 ... - CTOH; Sara, Fleury (Odatis, 2015)
EASE-grid monthly map with a spatial resolution of 12.5 km covering the CryoSat-2 flight period 2010-2017 from 65°N to 88°N. Includes the following parameters: sea_ice_thickness sea_ice_thickness_unc snow_density_W99 snow_depth_W99_corrected sea_ice_myi_fraction sea_ice_density ...